Comparison of Kenya and Ethiopia's Foreign Policies in Response to the Rivalry Between the Great Powers in the Indo-Pacific - Yosua Saut Marulitua Gultom; Rizky Hikmawan (Institute of International Studies, 2025)
The transformation of the Asia-Pacific region into the Indo-Pacific has significant implications, expanding the scale of power competition between the United States and its allies and China. This expansion of competition has reached countries in East Africa, including Kenya and Ethiopia. This study seeks to examine how Kenya and Ethiopia respond to the great power rivalry in the Indo-Pacific. This is done using Type III neoclassical realism theory, which argues that structural stimuli such as great power rivalry in the Indo-Pacific will be filtered at the domestic level to achieve foreign policy outcomes. To achieve an objective study, the author employs a comparative qualitative method. Data is collected through literature review, utilizing primary sources such as state speeches, government statements, legal documents, and official reports. These primary sources are further supported by additional sources such as journal articles and news reports. Kenya and Ethiopia exhibit contrasting foreign policies due to differing domestic structures. Kenya employs a pragmatic hedging strategy, engaging multiple powers like the US for military cooperation and China for infrastructure. This multi-alignment is rooted in its diplomatic culture and institutionalized political system with checks and balances. Conversely, Ethiopia's foreign policy is assertive and transactional, prioritizing regime survival. Driven by personalized leadership and weak institutions, it relies heavily on China while having strained relations with the US. Ultimately, domestic filters in neoclassical realism explain Kenya's calculated approach versus Ethiopia's unpredictable, unilateral actions.